The comprehension of clitic gender in child heritage and second language Spanish: evidence from a dual language program - Austin, Jennifer; Thane, Patrick D.; Rodríguez, Stephanie A.; Goldin, Michele (Frontiers in Language Sciences, 2024)
Despite the growth of dual-language programs in the United States, few studies have examined how children acquire Spanish through immersion. This article compares how heritage speakers (HS) and English-fluent Spanish L2 learners (L2L) immersed in Spanish comprehend gender in direct object clitics, an area of Spanish grammar prone to bilingual effects. A total of 78 English-dominant children enrolled in a dual language school participated in the experiment: 24 HS (6 in 2nd grade, 10 in 4th/5th grade, 8 in 7th/8th grade) and 54 L2L (16 in 2nd grade, 20 in 4th/5th grade, 18 in 7th/8th grade). Participants completed a forced-choice task which tested their ability to select target-like clitic gender after hearing sentences such as ‘La niña está tocando la guitarra (feminine). ¿Qué hace?' The girl is playing the guitar (feminine). What does she do? * ‘Lo toca' (masculine singular clitic)/ ‘La toca' (feminine singular clitic) She plays it. Results did not reveal any significant differences at the p < 0.05 level between the HS and L2L groups with accuracy in clitic gender. We found that in receptive knowledge of masculine clitic gender, the HS and L2L children had very similar scores in the 2nd grade and showed a similar improvement in accuracy by the 7th/8th grades. However, we did not find a similar pattern of growth in children's ability to select target-like feminine gender in either group. We discuss our findings and propose possible implications for immersion programs.